2017
DOI: 10.1016/j.pediatrneurol.2016.09.016
|View full text |Cite
|
Sign up to set email alerts
|

mTOR Inhibition Mitigates Molecular and Biochemical Alterations of Vigabatrin-Induced Visual Field Toxicity in Mice

Abstract: BACKGROUND Gamma-vinyl–γ-aminobutyric acid (GABA) (vigabatrin) is an antiepileptic drug and irreversible GABA transaminase inhibitor associated with visual field impairment, which limits its clinical utility. We sought to relate altered visual evoked potentials associated with vigabatrin intake to transcriptional changes in the mechanistic target of rapamycin (mTOR) pathway and GABA receptors to expose further mechanisms of vigabatrin-induced visual field loss. METHODS Vigabatrin was administered to mice via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…We hypothesized that in SSADHD, postnatal seizures were caused by overexpression of NKCC1 and a continuing excitatory capacity of GABA A receptors after birth. If confirmed, this mechanism would explain the paradox of seizures in a hyperGABAergic condition (Vogel et al 2017c). Furthermore, it would also suggest that inhibition of NKCC1 might have positive therapeutic effects in SSADHD.…”
Section: The Paradox Of Seizures In a Ssadhd A Hypergabaergic Disordermentioning
confidence: 90%
See 2 more Smart Citations
“…We hypothesized that in SSADHD, postnatal seizures were caused by overexpression of NKCC1 and a continuing excitatory capacity of GABA A receptors after birth. If confirmed, this mechanism would explain the paradox of seizures in a hyperGABAergic condition (Vogel et al 2017c). Furthermore, it would also suggest that inhibition of NKCC1 might have positive therapeutic effects in SSADHD.…”
Section: The Paradox Of Seizures In a Ssadhd A Hypergabaergic Disordermentioning
confidence: 90%
“…A number of gene expression changes correlated between the two animal models. Prkag1 was down-regulated in brain of both models (Vogel et al 2017b; 2017c). Prkag1 is a gamma regulatory subunit of the heterotrimeric AMP-activated protein kinase (AMPK), which also contains an alpha catalytic subunit and a non-catalytic beta subunit (Fig.…”
Section: Future Directionsmentioning
confidence: 94%
See 1 more Smart Citation
“…The role(s) of GABA, β‐alanine and 4‐GBA in the ocular toxicity of VGB remain unknown. Conversely, we and others have demonstrated that supraphysiological GABA impacts the mTOR pathway of autophagy, leading to mitochondrial accumulation and enhanced oxidative stress . β‐Alanine, the structural homologue of GABA, has GABAergic and glycinergic roles that are well‐described, but its role in VGB‐mediated toxicity has not been investigated.…”
Section: Discussionmentioning
confidence: 90%
“…Long‐term VGB intervention associates with peripheral atrophy of the retinal nerve fiber layer, and rodents similarly treated manifest disorganization of the photoreceptor nuclear layer and cone photoreceptor damage . It has been suggested that VGB‐induced elevation of ocular/retinal GABA induces excitotoxicity via GABAergic receptors, resulting in oxidative stress . Other studies have suggested globus pallidi and white matter anomalies associated with chronic VGB intake, and pathological roles for amino acids (ornithine, taurine) that share structural and biochemical properties of GABA have also been implicated in VGB‐associated ocular toxicity .…”
Section: Discussionmentioning
confidence: 99%